The effect of 6-weeks competition period training on body composition of boxers - Akgul, M. N.; Cakmakci, O. (Turkish Journal of Sport and Exercise, 2017)
The aim of this study to investigate the effects of 6-weekscompetition period training on body composition of elite boxers. In this study, 9 elite boxers from the boxing team of the Selçuk University volunteered. Subjects were of mean age 24.11 ± 4.14 years, the experience of training 7.11 ± 3.06 years and height 179.12 ± 6.72 cm. Boxing training of the competition period was conducted for 6-weeks. The effects of the competition period training on body composition were evaluated as related to pre- and post-test data. Tanita TBF-410 Body Composition Analyzer was used to determine the parameters of subjects` body composition [VA (kg), BMI (kg/m2), BMR (kcal), FAT (%), FMASS (kg), FFM (kg), TMV (kg)]. For data analyses, SPSS 22.0 statistical package program was operated. Mean and standard deviation were computed. According to tests of normality, the Independent t-test was used to compare paired groups. The level of statistical significance was set at 0.05. When the pre-test and post-test parameters were compared, body weight and BMI in pre-test were lower than post-test (p<0.05). No significant difference between pre-test and post-test for BMR, FAT, FMASS, and TMW (p>0.05). In conclusion, the recent study suggests that a 6-weeks training of competition period in elite boxers might decrease body weight and BMI but it might not have any effect on other parameters.